Consumer Confusion : The Choice of AFORE - Schwartz, Moises; Calderon-Colin, Roberto; Dominguez, Enrique (Washington, D.C. : International Monetary Fund, 2008)
This paper was prepared for the World Bank 4th Annual Contractual Savings Conference (Washington DC, April 2008) co-organized by Gregorio Impavido (gimpavido@imf.org). The article shows that account transfers among pension administrators in Mexico barely respond to price or return considerations and in general has not improved the consumer's pension balance. Instead of strengthening competition through lower fees and higher returns for the consumer, AFORE switching has so far undermined the system and resulted in the destruction of value. Moreover, "noisy" evaluations of the product by the consumer tend to undermine the power of competition. Thus, an increased number of pension fund managers has not provided a more competitive environment. The theoretical framework allows for the estimation of "noise" and mark-ups in the AFORE industry. As the number of AFOREs increases, the mark-up diminishes at a very slow rate. This implies that more participants in the industry will hardly affect prices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet